Feasibility and Safety of Outpatient Total Laparoscopic Hysterectomy - Maheux-Lacroix, Sarah (JSLS, 2015)
BACKGROUND AND OBJECTIVE: Ambulatory total laparoscopic hysterectomy (TLH) could lead to significant cost savings, but some fear the effects of what could be premature postsurgical discharge. We sought to estimate the feasibility and safety of TLH as an outpatient procedure for benign gynecologic conditions. METHODS: We report a prospective, consecutive case series of 128 outpatient TLHs performed for benign gynecologic conditions in a tertiary care center. RESULTS: Of the 295 women scheduled for a TLH, 151 (51%) were attempted as an outpatient procedure. A total of 128 women (85%) were actually discharged home the day of their surgery. The most common reasons for admission the same day were urinary retention (19%) and nausea (15%). Indications for hysterectomy were mainly leiomyomas (62%), menorrhagia (24%), and pelvic pain (9%). Endometriosis and adhesions were found in 23% and 25% of the cases, respectively. Mean estimated blood loss was 56 mL and mean uterus weight was 215 g, with the heaviest uterus weighing 841 g. Unplanned consultation and readmission were infrequent, occurring in 3.1% and 0.8% of cases, respectively, in the first 72 hours. At 3 months, unplanned consultation, complication, and readmission had occurred in a similar proportion of inpatient and outpatient TLHs (17.2%, 12.5%, and 4.7% versus 18.1%, 12.7%, and 5.4%, respectively). In a logistic regression model, uterus weight, presence of adhesions or endometriosis, and duration of the operation were not associated with adverse outcomes. CONCLUSION: Same-day discharge is a feasible and safe option for carefully selected patients who undergo an uncomplicated TLH, even in the presence of leiomyomas, severe adhesions, or endometriosis.